The efficacy and safety of continuous intravenous tirofiban for acute ischemic stroke patients treated by endovascular therapy: a meta-analysis - Wang, Mengmeng; Li, Jing; Zhang, Lingyu; Li, Nana; Li, Xuemei; Wang, Pengfei (Frontiers in Neurology, 2024)
Introduction: Tirofiban is a non-peptide selective glycoprotein IIb/IIIa receptor inhibitor with a short half-life. The research assesses the efficacy and safety of continuous intravenous tirofiban in patients with acute ischemic stroke (AIS) undergoing endovascular therapy (ET). Methods: A systematic search of Pubmed, Embase, Web of Science, and Cochrane Library databases is conducted from inception until January 26, 2024. Eligible studies are included based on predefined selection criteria. Efficacy outcomes (favorable functional outcome and excellent functional outcome) and safety outcomes (symptomatic intracranial hemorrhage [sICH], any intracranial hemorrhage [ICH], and 90-day mortality) are calculated using odds ratios (OR) and 95% confidence intervals (CI). Results: A total of 4329 patients from 15 studies are included in the analysis. The results show a significant trend towards favorable functional outcomes in the tirofiban group (OR, 1.24; 95% CI, 1.09-1.42; p = 0.001). In terms of safety outcomes, tirofiban does not increase the risk of sICH (OR, 0.90; 95% CI, 0.71-1.13; p = 0.35) or any ICH (OR, 0.97; 95% CI, 0.70-1.34; p = 0.85), but significantly decreased 90-day mortality (OR, 0.75; 95% CI, 0.64-0.88; p = 0.0006). Subgroup analysis suggests that continuous intravenous tirofiban demonstrates better efficacy (OR, 1.24; 95% CI, 1.09-1.42; p = 0.001) for AIS patients undergoing rescue ET with even better results when used in combination with intra-arterial and intravenous administration (OR, 1.25; 95% CI, 1.07-1.451; p = 0.005). Conclusion: Continous intravenous tirofiban is effective and safe for AIS patients undergoing rescue ET, particularly when combined with intra-arterial tirofiban.